Analysis of The Application Of E-SPT in The Annual Tax Return Reporting of Corporate Taxpayers at The Medan City Primary Tax Office - Putri Kemala Dewi Lubis; Eliza Putri (Asosiasi Dosen Akuntansi Indonesia, 2020)
This research aims to find out the application of the e-SPT PPh agency in KPP Pratama Medan Kota and cause the Taxpayer Agency not to deliver the annual SPT through e-SPT at the Medan Kota Primary Tax Service Office. The approach used in this study uses quantitative descriptive, and the data collection techniques used in this study are documentation and interview techniques. Data is analyzed by collecting the data of the taxpayer of the agency, calculating the percentage of corporate taxpayers who report annual SPT through manuals and e-SPT and conducting analysis of the results obtained. The results showed that many Corporate Taxpayers do not report SPT through e-SPT due to the electronic SPT reporting system frequent database error and lack of understanding of the Taxpayer Agency about reporting SPT through e-SPT as well as taxpayer indifference to its tax obligations. Taxpayers do not know about tax penalties such as administrative sanctions (fines, interest) or criminal sanctions that it obtains due to negligence in reporting the agency's annual SPT.